Factors Affecting The Cost of Debt in Companies Listed within Kompas 100 - Muhamad Septian; Rosinta Ria Panggabean (Bina Nusantara University, 2016)
This study aims to determine the effect of Good Corporate Governance (GCG) which is proxied through the proportion of independent commissioners, managerial ownership, institutional ownership, quality audits, and family ownership on the cost of debt. The objects of this study are companies listed in Kompas 100 from the period of August 2013-January 2014. The method used to take samples of the study using purposive sampling method. Data analysis methods used are descriptive statistics, the classical assumption test, and hypotheses test. Based on the results of hypothesis testing that performed by using multiple regression analysis at the 0.05 significant level, the results of this study prove that the proportion of independent commissioners has a significant negative effect on the cost of debt. Also, managerial ownership has a significant positive effect on the cost of debt. On the other hand, institutional ownership, quality audits, and family ownership have no significant effect the cost of debt.